Analysis of an ISOPE-type dual algorithm for optimizing control and nonlinear optimization - Tadej, Wojciech; Tatjewski, Piotr (Zielona Góra: Uniwersytet Zielonogórski)
First results concerning important theoretical properties of the dual ISOPE (Integrated System Optimization and Parameter Estimation) algorithm are presented. The algorithm applies to on-line set-point optimization in control structures with uncertainty in process models and disturbance estimates, as well as to difficult nonlinear constrained optimization problems.
Keywords: nonlinear optimization; optimizing control; duality; condition number